MATHEMATICAL LITERACY PROFILE OF ELEMENTARY SCHOOL STUDENTS IN INDONESIA: A SCOPING REVIEW - Intan Putri Hapsari; Totok Victor Didik Saputro; Yosua Damas Sadewo (Institut of Shanti Bhuana, 2022)
Mathematical literacy becomed one of skills that had to be mastered by the students in this era. Mathematical literacy could start to be learned in elementary level. This study aimed to describe the research trends of mathematical literacy profile for elementary school students in Indonesia. This study used scoping review research with 5 steps including 1) identifying the initial research questions; 2) identifying relevant studies; 3) study selection; 4) charting and collating the data; and 5) summarizing and reporting the results. The data exploration process was taken through open-access websites such as Google Scholar, ERIC, and Springer using keywords “Literasi Matematika Siswa Sekolah Dasar”, “Mathematical Literacy of Elementary School Students in Indonesia”. The exploration process was also limited publication for 5 last years. The data reduction process was analyzed using the Preferred Reporting of Items for Systematic Review and Meta-Analyses (PRISMA). The study results were classified to the 3 components such as 1) research methodologies trends, 2) mathematical literacy development, and 3) student’s achievement based on mathematical literacy.